Analysis of Rating Positions of Insurance Companies on International and National Markets - POLOZOVA, Tetiana; LUTSKYI, Andrii; LUTSKYI, Myroslav; ZVARYCH, Roman; KOLІSNYK, Maksym (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
The purpose of the article is to analyze the rating positions of insurance companies. The article explores the development trends at the insurance services market of Ukraine. The paper contains review of the segmentation criteria for insurers according to the ‘The World’s Largest Public Companies’ methodology (diversified insurance, life and health insurance, property insurance and casualty insurance). This rating method applies a set of indicators such as income, sales, assets and market value of the company. The paper identified the leaders in each segment of the international insurance market in 2018. The research findings revealed the absence of Ukrainian companies in the rating because of their low potential and insufficient level of development. The authors conducted analysis of insurers’ positions at the national market in the rating reported by news portal ukrstrahovanie.com.ua. The main ranking approach is multi-factor analysis. This method employs the following indicators: assets; payout level; insurance funds; the share of premium collection from insurance classes; transparency of the insurer's statements. The information for the insurers’ rating was collected from the web-site of Mind business. The rating considers financial stability and business activity of insurance companies as main factors gathered from open public sources. The rating methodology consists of several factors that affect the attractiveness of insurance companies for the customers. The paper developed system of indicators for the rating of insurers in Ukraine according to the journal ‘Insurance TOP’ (insurance classes, economic indicators, business entities). The evidence shows potential for growth of domestic insurance enterprises at the national market but also the rankings confirmed low level of their competitiveness at the international market.